Benign Pediatric Jawbone Lesions: A 10-Year Clinical and Radiological Pilot Study - Emil Crasnean; Alina Ban; Mihaela Hedeșiu; Raluca Roman; Cristian Dinu; Mihaela Băciuț; Sergiu Văcăraș; Ileana Mitre; Oana Almășan; Vlad-I. Nechita; Gabriel Armencea; Simion Bran; et al. (MDPI AG, 2023)
This study aimed at presenting a retrospective longitudinal analysis of the pediatric jaw lesions treated at the Oral and Maxillofacial Surgery Clinic in Cluj-Napoca, Romania, over a timeframe of ten years (2012 to 2022). The clinical and radiological characteristics of the jawbone lesions, the treatment outcome, and the recurrence incidence were described. All consecutive patients aged below 18 years, with histologically diagnosed odontogenic tumors (OTs), nonodontogenic tumors (non-OTs), or odontogenic cysts (OCs) were included. Age, dentition type, clinical symptoms, preoperative and postoperative radiological tests, histological diagnosis, treatment, and follow-up information one year following the diagnoses were all examined. Eighty-two cases were included. The ratio of men to women was 1.15:1, with the mandible predominating by 64.4%. Inflammatory radicular cysts predominated in 31.7% of cases. A total of 42.68% of the patients were asymptomatic. Enucleation was the most frequent surgical technique (45.1%), followed by cystectomies (28%) and marsupialization (14.6%). The overall recurrence rate was 7.3%; the most recurrent histopathological lesion was the odontogenic keratocyst. This study sheds new light on the clinical and radiological characteristics, treatment outcomes, and recurrence rate of juvenile jawbone lesions in children and adolescents. The diagnosis and treatment of jawbone lesions in children and adolescents can be enhanced with the use of epidemiological, clinical, and imagistic information.